THE DIFFERENCE OF GRAMMATICAL ERROR IN WRITING RECOUNT TEXT BETWEEN NATURAL SCIENCE AND SOCIAL SCIENCE STUDENTS - Sembiring, Imantha Eko Putra; Gintings, Elia Masa (TRANSFORM: Journal of English Language Teaching and Learning, 2013)
ABSTRACT This study concerned on the difference of grammatical error in writing recount text between natural science and social science students. The objective of this study was to find out the difference of grammatical error in writing recount text between natural science and social science students. This research was conducted by using causal- comparative research. The subject of the study was the students of XI-IPA1 and XI- IPS1 of SMA Swasta Methodist Berastagi. The number of the samples was twenty eight. The techniques for data analysis were quantitative data. The t-result was 2,60 (bigger than t table 1,706). The conclusion is that there is a significant difference of grammatical error in writing recount text between natural science and social science students. Keywords: error, writing, causal-comparative